The rise and fall of sustainability in Western Australian politics: a review of sustainable development under the Western Australian Labor government between 2001 and 2008 - Brueckner, Martin; Pforr, Christof (ProQuest LLC (Bethesda), 2011)
This article addresses problems associated with the political operationalization of the sustainability agenda and the design of new development goals based on the case of Western Australia (WA). In this state, rapid economic development, long the key objective of successive governments, has caused serious environmental problems and brought into question the sustainability of the state's development path. In the 2001 WA state election, the Labor Party came into office in part because of its overt commitment to sustainable development, departing from past pro-growth philosophies. This article analyzes the extent to which the WA Labor government was able to operationalize politically its sustainability agenda during its time in office between 2001 and 2008. It finds that despite a strong commitment to its sustainability agenda in the early years of holding office, the Labor government failed to institutionalize policy changes, which, following a 2006 leadership change, allowed for a reversal of progress. We then discuss the WA experience within the global policy context and place it within the larger debates on the operationalization of sustainability.